Mitochondrial Dysfunction in Arrhythmia and Cardiac Hypertrophy - Xiaomei Wang; Qianxue Yu; Xuemei Liao; Mengying Fan; Xibin Liu; Qian Liu; Manru Wang; Xinyu Wu; Chun-Kai Huang; Rubin Tan; Jinxiang Yuan (Reviews in Cardiovascular Medicine, 2023)
Arrhythmia and cardiac hypertrophy are two very common cardiovascular diseases that can lead to heart failure and even sudden death, thus presenting a serious threat to human life and health. According to global statistics, nearly one million people per year die from arrhythmia, cardiac hypertrophy and other associated cardiovascular diseases. Hence, there is an urgent need to find new treatment targets and to develop new intervention measures. Recently, mitochondrial dysfunction has been examined in relation to heart disease with a view to lowering the incidence of arrhythmia and cardiac hypertrophy. The heart is the body’s largest energy consuming organ, turning over about 20 kg of adenosine triphosphate (ATP) per day in the mitochondria. Mitochondrial oxidative phosphorylation (OXPHOS) produces up to 90% of the ATP needed by cardiac muscle cells for contraction and relaxation. Dysfunction of heart mitochondria can therefore induce arrhythmia, cardiac hypertrophy and other cardiovascular diseases. Mitochondrial DNA (mtDNA) mutations cause disorders in OXPHOS and defects in the synthesis of muscle contraction proteins. These lead to insufficient production of secondary ATP, increased metabolic requirements for ATP by the myocardium, and the accumulation of reactive oxygen species (ROS). The resulting damage to myocardial cells eventually induces arrhythmia and cardiac hypertrophy. Mitochondrial damage decreases the efficiency of energy production, which further increases the production of ROS. The accumulation of ROS causes mitochondrial damage and eventually leads to a vicious cycle of mitochondrial damage and low efficiency of mitochondrial energy production. In this review, the mechanism underlying the development of arrhythmia and cardiac hypertrophy is described in relation to mitochondrial energy supply, oxidative stress, mtDNA mutation and Mitochondrial dynamics. Targeted therapy for arrhythmia and cardiac hypertrophy induced by mitochondrial dysfunction is also discussed in terms of its potential clinical value. These strategies should improve our understanding of mitochondrial biology and the pathogenesis of arrhythmia and cardiac hypertrophy. They may also identify novel strategies for targeting mitochondria in the treatment of these diseases.